Environmental Degradation of the Loji River in Pekalongan City and the Emergence of a Community Movement 1980–2014 - Ani Aprilianti; Nina Witasari (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to examine the factors of environmental changes that occurred in the Loji River as well as community memories regarding the river in the 1980s until the emergence of a community movement. This research employs the historical method which consists of four stages: heuristics, criticism, interpretation, and historiography. In addition, this study also uses the oral history method to explore community memories regarding the condition of the river in the 1980s. Changes in the condition of the Loji River began to appear in the 1990s. These changes were marked by the use of the river as a disposal site for textile and household waste, the decrease in water discharge due to the construction of diversion channels, and the narrowing of the river caused by development along in the riverbanks. Community memories indicate that in the 1980s the Loji River was still in relatively good condition and was used for various daily activities, such as bathing, washing, swimming, and fishing. However, the condition of the river gradually declined until in 2014 a community movement emerged through the establishment of the Komunitas Peduli Kali Loji (KPKL). This community was founded as a from of public concern for the condition of the Loji River in Pekalongan City by carrying out various activities, one of which is river clean-up actions as an effort to encourage the community to maintain the cleanliness and sustainability of the river.